Analisa Pengelompokan Dataset Komputer Menggunakan Algoritma X-Means - Rokhmatan Khaerullah, Rizal; Suarna, Nana; Nurdiawan, Odi (PT. Bangun Harapan Bangsa, 2023)
Computer dataset cluster analysis is a data mining technique that aims to identify a group of objects that have the same characteristics. The problem in this research is how to implement the X-Means Clustering algorithm in grouping computer datasets based on computer prices and specifications. The purpose of this study is to determine the implementation of the X-Means Clustering method in classifying computer datasets against prices and specifications. This computer dataset consists of several attributes with a large number of records so we need a process that can group the data, namely clustering. The use of clustering is expected to provide predictions on the grouping of the computer dataset. One of the clustering methods that can be used to group data is X-Means clustering. The results of the research from data mining grouping computer datasets with the x-means Cluster model produced as many as 3 clusters, namely cluster 0 with 710 members, cluster 1 with 136 items and cluster 2 with 15 items. Keywords: Cluster X-Means Algorithm